Effect of Momordica charantia Linn. leaf and fruit juice on fertility in male mice - Ampa Luangpirom; Watchara Kourchampa; Pichet Somsapt (International Journal of Phytomedicine, 2015)
Fertility effect of Momordica charantia Linn. leaf and fruit juice at doses of 200, 400 and 600 mg/ 100 gBW were evaluated by determining blood prolactin (PRL) and testosterone (T) levels, and sperm quality in male mice after 21 days of oral administration. The increase in PRL and decrease in T levels were found to be dose dependent in both treatments. Meanwhile, the sperm quality impairment was found in group receiving fruit juice was more severe than that of groups receiving leaf juice. Interestingly, the potency of testicular dysfunction was related to the degree of alteration of reproductive hormones. In conclusion, M. charantia leaf and fruit juice may cause testicular dysfunction, which indirectly affects pituitary PRL synthesis and consequently impaired testicular T synthesis. The use of M. charatia products at high dose in traditional medicine should include a caution about this adverse effect, especially in long term treatment.